Analisa Perubahan dan Perbaikan Sistem Kerja Serta Budaya Perusahaan dengan Fast Start dan 5R pada SPP KRW PT X - Surya Adinata Jackson Susanto; Jani Rahardjo (Jurnal Titra, 2018)
The purpose of this thesis are to analyzing the change and improvement of company work system and culture through the fast start and 5R implementation at SPP KRW. The aim for fast start implementation are developing zero loss mindset and 100% employee ownership capabilities. 5R culture improvements are given to for completing company KPI target and supporting the capabilities development of zero loss mindset. Actual data observation shows that only 52% of fast start key principles area implemented and the 5R score at SPP KRW is 2,41 at 2018 first week, which is below the KPI target of 3. Changes and improvement through the fast start implementation are done in 3 steps and for the 5R in 5 steps, which is refer to each “R”. Changes and improvement implementation has improving the fast start implementation progress to 86% and improving 5R average score with 0,06 point at 2018 15th week. The results of research concluding that the capabilities of zero loss mindset and 100% employee ownership are implemented at SPP KRW work system by the fast start project. The result for the 5R improvement are showing the rising trend of 5R score and supporting the zero loss mindset capabilities building.